Rebounding strategies in basketball - Okubo, H.; Hubbard, M. (Procedia Engineering, 2014)
A three dimensional dynamic model is used to estimate the best rebounding position for players in basketball. The model has six distinct sub-models: flight, and ball-contact sub-models of ball-rim, ball-bridge, ball-board, ball-bridge-board, and ball-rim- board contact. It allows both slipping and non-slipping interactions at the ball-contact point. Using probabilistic selection of release velocity, angle, and lateral deviation angle, simulations analyse ball trajectories and good rebounding positions for players. Our estimation includes player wingspan. We analyse the relationship between the most likely player rebound positions and ball rebound positions with high probability. The best player rebound position is usually different from the most likely ball rebound position. Player rebound regions for players with large wingspans are very close to the hoop and include some likely ball rebound positions. For short-range shots, one player is able to collect almost all of rebounding balls but two or three rebounders are required for long-range shots.